CHANGE OF POLITICAL SYSTEM: MODERNIZATION OF DEMOCRACY TO MERITО-DEMOCRACY PAPER AT SOCIOLOGY OF POLITICS: CHANGE OF POLITICAL SYSTEM: MODERNIZATION OF DEMOCRACY TO MERITО-DEMOCRACY PAPER AT SOCIOLOGY OF POLITICS - Ilieva , Sonya (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
24 years after the changes in Bulgaria nationals are again in the streets calling for change in the system. The public debate is clear that this change is meant only as a change in the voting system - from party lists to the majority model. The author of the paper, however, believes that it is not only this, but for a comprehensive review of the democratic model to be placed in the light of meritocracy. The basic idea is the following: is needed modernization of democracy as a system based on meritocratic elements. This is a reasonfor a new type The Social Contract - a fusion of the positive components of meritocracy and democracy. This means to keep the basic democratic values of democracy, but to give power of knowing their proven expertise and intellectual people to be defined by democratic election procedures competitions to fill the positions and test expertise.